"Because we all change, right?": A narrative inquiry of an international student's self-formation in South Korea. (January 2023) - Kudaibergenov, Meerbek
Abstract: Prior research on international student identity formation has mainly focused on students in Western countries, predominantly, the USA, the UK and Australia, leaving international students in Asia largely under-represented. This article, on the other hand, explores identity formation in an Asian context through a narrative inquiry of an international student, Mary (pseudonym), studying in South Korea (Korea hereafter). Drawing on Marginson's (2014) concept of self-formation in international education, it examines Mary's lived experiences as a cross-border student and presents a story of her personal transformation. Insights presented in this inquiry highlight that identity formation for international students is an increasingly dynamic process of conscious making of the self amid the glees and tensions that international education has to offer. Additionally, this work emphasizes that identity negotiation is triggered by contradictions of personal-versus-contextual and suggests the need to consider ways to strengthen agency in international students to facilitate self-change and development. Highlights: International student population has been increasing steadily in South Korea. Self-formation framework was used to understand student identity formation. Identity negotiation is triggered by contradictions of personal-versus-contextual. Student identity formation avails itself of multiplicity and hybridity. Student agency must be foregrounded in research and supported/enhanced in practice.